An integrated workflow for 2D and 3D posture analysis during vestibular system testing in mice - Wan, Yong; Edmond, Michaela A.; Kitz, Colin; Southern, Joseph; Holman, Holly A. (Frontiers in Neurology, 2023)
YW and HAH formulated overarching goals and aims. HAH, CK and JS conducted balance beam and rotarod testing, YW curated AI data. YW, ME, and HAH performed analysis. YW performed formal analysis of mathematical and computational techniques. YW, CK, JS and HAH performed data collection. YW developed software, designed computer programs and implemented computer code and AI. HAH supervised, managed and coordinated research. ME and PSP verified replication and reproducibility of results. YW wrote the initial draft, ME, and HAH provided additional draft content and editing.We have designed a workflow integrating computation and visualization tasks for 2D and 3D posture analysis of mice traversing a balance beam for enhanced vestibular function testing. This work contributes to the Frontiers in Neurology, Computational Neuroscience Approaches in Neuro-Otology, by providing a foundation for examining the vestibular system and motor coordination by artificial intelligence (AI) and machine learning (ML). Currently, active vestibular function testing is based on well-established protocols, rotarod and balance beam tests, with only two outputs: speed and distance. A posture analysis tracks mouse movements as body joints (also known as keypoints, such as feet, body, head, ears, and tail) in each frame of a video to detect subtle changes in vestibular function and motor coordination, such as imbalance and foot slips. Unsteadiness, imbalance, or loss of equilibrium are often accompanied by spatial disorientation, which are leading symptoms of vestibular dysfunction. There are no cures for vestibular disorders, but current treatments include managing symptoms with medications and vestibular rehabilitation. This work approaches detecting vestibular dysfunction at earlier stages with higher accuracy, which can lead to early intervention.